Transfer of pyrrolizidine alkaloids from ragwort, common groundsel and viper's bugloss to milk from dairy cows. Issue 11 (1st November 2020) - Mulder, Patrick P.J.; Klijnstra, Mirjam D.; Goselink, Roselinde M.A.; van Vuuren, Ad M.; Cone, John W.; Stoopen, Geert; Hoogenboom, Ron L.A.P.
ABSTRACT: To investigate the transfer of pyrrolizidine alkaloids (PAs) from feed to milk, rumen-cannulated dairy cows were intra-ruminally fed with 200 g/day of dried plant material of either ragwort (mixture of Jacobaea vulgaris and Senecio inaequidens ), common groundsel ( Senecio vulgaris ) or viper's bugloss ( Echium vulgare ) for a period of 4 days. PA levels in the plant materials were 3767, 2792 and 1674 µg g −1 respectively. Feed intake, milk yield and several blood parameters indicative for liver function were not influenced by the treatment. When fed ragwort, increased levels of PAs were detected in the milk, in particular jacoline and an unidentified cyclic diester, possibly a hydroxylated metabolite from retrorsine. The latter was the most important PA in milk from cows fed common groundsel. For viper's bugloss, echimidine was the most abundant identified PA but in addition several hydroxylated PA metabolites were detected. For ragwort, the overall PA transfer was estimated at 0.05% and 1.4% for jacoline (N-oxide). Transfer rates were similar for viper's bugloss (0.05%) but lower for common groundsel (0.01%). Only a small portion of the administered PAs was quantified in milk, urine and faeces, with an overall balance of 4.5%, 2.9% and 5.8%, for ragwort, common groundsel and viper's bugloss, respectively. Samples taken from the rumen indicated that the N-oxides were converted into the free bases, which was confirmed by in vitro studies with the same plant species incubated with ruminal fluid. These results confirm that the transfer of PAs to milk is relatively low but may be of concern for human health regarding the genotoxic and carcinogenic properties of these compounds. The transfer rate depends on the type of PAs present in the weeds. The incomplete balance of input vs output stresses the need to further investigate the metabolism and the potential transfer of metabolites into edible products.